The role of p53 in progression of cutaneous squamous cell carcinoma - Piipponen Minna; Riihilä Pilvi; Nissinen Liisa; Kähäri Veli-Matti (MDPI, 2022)
Skin cancers are the most common types of cancer worldwide, and their incidence is increasing. Melanoma, basal cell carcinoma (BCC), and cutaneous squamous cell carcinoma (cSCC) are the three major types of skin cancer. Melanoma originates from melanocytes, whereas BCC and cSCC originate from epidermal keratinocytes and are therefore called keratinocyte carcinomas. Chronic exposure to ultraviolet radiation (UVR) is a common risk factor for skin cancers, but they differ with respect to oncogenic mutational profiles and alterations in cellular signaling pathways. cSCC is the most common metastatic skin cancer, and it is associated with poor prognosis in the advanced stage. An important early event in cSCC development is mutation of the TP53 gene and inactivation of the tumor suppressor function of the tumor protein 53 gene (TP53) in epidermal keratinocytes, which then leads to accumulation of additional oncogenic mutations. Additional genomic and proteomic alterations are required for the progression of premalignant lesion, actinic keratosis, to invasive and metastatic cSCC. Recently, the role of p53 in the invasion of cSCC has also been elucidated. In this review, the role of p53 in the progression of cSCC and as potential new therapeutic target for cSCC will be discussed.